Music supported therapy promotes motor plasticity in individuals with chronic stroke - Ripollés, P.; Rojo, N.; Grau-Sánchez, J.; Amengual, J. L.; Càmara, E.; Marco-Pallarés, J.; Juncadella, M.; Vaquero, L.; Rubio, F.; Duarte, E.; Garrido, C.; Altenmüller, E.; et al. (Brain imaging and behavior, 2016)
Novel rehabilitation interventions have improved motor recovery by induction of neural plasticity in individuals with stroke. Of these, Music-supported therapy (MST) is based on music training designed to restore motor deficits. Music training requires multimodal processing, involving the integration and co-operation of visual, motor, auditory, affective and cognitive systems. The main objective of this study was to assess, in a group of 20 individuals suffering from chronic stroke, the motor, cognitive, emotional and neuroplastic effects of MST. Using functional magnetic resonance imaging (fMRI) we observed a clear restitution of both activity and connectivity among auditory-motor regions of the affected hemisphere. Importantly, no differences were observed in this functional network in a healthy control group, ruling out possible confounds such as repeated imaging testing. Moreover, this increase in activity and connectivity between auditory and motor regions was accompanied by a functional improvement of the paretic hand. The present results confirm MST as a viable intervention to improve motor function in chronic stroke individuals.